Assessment of Maximum Mouth Opening among Students of College of Dentistry/Babylon University - Ahmed S. Hameed Al-Noaman (Kufa Journal for Nursing Sciences)
Objectives: This study investigated the maximum mouth opening and its correlation with age among male and female students of college of dentistry, Babylon University. Patients and methods: A total of 317 students (140 males and 177 females) age ranged 20-25 years were recruited in this study. Each student was asked to open his/her mouth as wide as possible. The distance between the incise edge of upper right central incisor and the opposing tooth of the lower jaw was measured using a manual caliper. Results: The maximum mouth opening was 58 mm ±7.21 and 42 mm ±6.98 for males and females, respectively. The maximum mouth opening of males is significantly larger than that of female (P= 0.000). For males the highest value of mouth opening was observed in the age 23 years and a negative and insignificant (P=0.472) correlation was seen in the ages (24 and 25 years). For females the maximum mouth opening was noticed in the age of 20 years and a significant decreased (P=0.000) of mouth opening was observed then after. Conclusion: Males have wider mouth opening compared to females. Maximum mouth opening for males and females decreased with age. However, regardless the gender, non-specific correlation was observed between age and mouth opening. Recommendation: Further study to clarify the effect of age on mouth opening and the correlation between mouth opening and body weight.